Water-energy-carbon coupling relationships and barrier analysis: an empirical study based on China - Liu, Jinhua; Pan, Pei (Frontiers in Earth Science, 2025)
IntroductionExploring the synergistic development of water resources, energy, and carbon dioxide (CO₂)—the WEC nexus—is essential for promoting regional sustainable development.MethodsUsing an obstacle degree model, this study identifies key barriers affecting the WEC nexus in China and predicts the future trend of its coupling coordination degree.ResultsThe findings reveal: (1) From 2008 to 2022, the integrated development level of the WEC nexus in China exhibited a fluctuating upward trend, led by the carbon system and hindered by the energy system. (2) The coupling coordination degree improved from 0.47 in 2008 to 0.53 in 2022, shifting from near imbalance to marginal coordination. Spatially, the southeast outperformed the northwest, and the overall pattern displayed inertial dependence. (3) The main obstacle factors remained relatively stable over time. Specifically, water development was limited by per capita water resources and groundwater proportion; energy by per capita energy production and self-sufficiency; and carbon by investment in environmental governance and green space availability. (4) Projections for 2026–2035 indicate continued improvement in coupling coordination, although enhanced integration policies in water management, energy transition, and carbon reduction are required.DiscussionThis study contributes actionable insights for policy-making and supports ecological-economic synergies through spatial and obstacle-based analysis.